La técnica Delphi: Un método de consenso para la investigación en servicios de salud en Latino América - Palmieri, Patrick A. (2017)
The consensus method is an infrequently utilized group of research techniques for health services research in Latin America. The consensus method derives provides researchers with the ability to achieve a quantitative estimate through a qualitative approach. The consensus method represents an epistemological approach to the inexact sciences. The consensus method, including the nominal group and Delphi techniques, are useful when expert agreement on the formulation of recommendations is required, especially when scientific evidence is unavailable, existing evidence is disputed, or there is a little risk-benefit balance. The overall goal is to arrive at a valid conclusion, or consensus, from a repetitive group deliberation in response to a well-defined research question. The Delphi technique is an essential method to achieve consensus in areas where none previously existed, or the evidence is limited, low quality, and/or subject to debate. There are four general areas when researchers should consider the Delphi technique, including 1) The research problem does not lend itself to precise analytical techniques but can benefit from subjective judgments on a collective basis; 2) The research population presents diverse backgrounds with respect to experience and expertise; 3) More subjects are required than can effectively interact face-to-face; and 4) Time, costs, and logistics would make frequent meetings of all subjects unfeasible. The Delphi technique creates a structured environment for experts to review the best available information specific to a research question to formulate solutions to answer the question through a robust process. Overall, the Delphi technique is a powerful qualitative research method that needs to be utilized in Latin American health services research.